2015
DOI: 10.1021/es503842w
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Processes Ruling the Bioavailability of Zn to Roots of Euphorbia pithyusa L. Pioneer Plant

Abstract: Euphorbia pithyusa L. was used in a plant growth-promoting assisted field trial experiment. To unravel the microscopic processes at the interface, thin slices of E. pithyusa roots were investigated by micro-X-ray fluorescence mapping. Roots and rhizosphere materials were examined by X-ray absorption spectroscopy at the Zn K-edge, X-ray diffraction, and scanning electron microscopy. Results indicate some features common to all the investigated samples. (i) In the rhizosphere of E. pithyusa, Zn was found to exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 57 publications
3
31
1
1
Order By: Relevance
“…In this study, SEM and EDS analysis showed the presence of a mineral rim made up of Al-silicates coating the epidermis of H. tyrrhenicum roots (Figure 2), as previously observed in other autochthonous plant species growing in similar environments, like E. pithyusa subsp. cupanii, P. lentiscus, P. australis, and J. acutus [23,[76][77][78]109]. This structure was also detected by STXM ( Figure 6), also showing that Zn is mainly stored in the root epidermis.…”
Section: Mineral Rim At the Root-rhizosphere Interface And Zn Chemicamentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, SEM and EDS analysis showed the presence of a mineral rim made up of Al-silicates coating the epidermis of H. tyrrhenicum roots (Figure 2), as previously observed in other autochthonous plant species growing in similar environments, like E. pithyusa subsp. cupanii, P. lentiscus, P. australis, and J. acutus [23,[76][77][78]109]. This structure was also detected by STXM ( Figure 6), also showing that Zn is mainly stored in the root epidermis.…”
Section: Mineral Rim At the Root-rhizosphere Interface And Zn Chemicamentioning
confidence: 64%
“…XAS spectra for each sample were collected at least in triplicate for averaging and statistics. According to literature data [23,26,50,52,[74][75][76][77][78], in the soil-plant system, Zn can occur in different coordination environments, both bound to organic compounds (e.g., organic acids, phytochelatins, metallothioneins, etc.) and to inorganic molecules (e.g., sulfur, sulfate, carbonate, etc.)…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%
“…Soft X-ray Microscopy combined with Low Energy XRF LEXRF mapping analyses (STXM) were performed at the TwinMic (Kaulich et al, 2006;Gianoncelli et al 2016a and b) beamline at ELETTRA, Trieste (Italy) on plant root samples (see De Giudici et al, 2015 andMedas et al, 2015 for a detailed description on root sections preparation). The TwinMic microscope was operated in Scanning Transmission mode (Gianoncelli et al, 2009(Gianoncelli et al, , 2013(Gianoncelli et al, , 2006Morrison et al, 2006).…”
Section: Plants and Rhizosphere Solid Materials Collection And Analysismentioning
confidence: 99%
“…The plant is grown in a mine site and accumulates different metals. [28] The same root area was mapped simultaneously with both the standard TwinMic LEXRF system and the novel detector system under development. For this measurement, two of the eight SDDs of the standard TwinMic LEXRF system were replaced by one trapezoid containing six hexagonal monolithic SDD elements.…”
Section: Resultsmentioning
confidence: 99%